The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1051/matecconf/201710806001
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Micro-V-Bending

Abstract: Abstract. Bending in sheet metal forming is defined as uniformly straining process around a linear axis. A V-bending process is normally used in sheet metal working due to the tool and process simplicity. The main problem in bending process is a springback occurrence which causes an error in part dimension. In a micro level, the springback angle is difficult to be assessed because of the influence of size effects in all aspects of the system. The springback behavior has been investigated in many previous kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Misi yang keempat adalah meningkatkan keterampilan belajar efektif, ini berkaitan dengan bimbingan belajar. Menurut Santi et al (2017) Berdasarkan hasil wawancara bahwa terkadang ada peserta didik yang datang bukan berdasarkan pada kebutuhan yang telah di asesmen, maka setidaknya guru BK perlu memiliki berbagai kompetensi konselor sehingga hal tersebut bisa ditangani dengan baik. Selain itu, aspek kebutuhan lain yang tidak kalah penting adalah bagaimana mendukung program pemerintah melalui Kurikulum Merdeka dengan mencegah terjadinya 3 dosa besar Pendidikan seperti bullying, kekerasan seksual, dan intolerasi, ditambah dengan pencegahan terhadap obat-obatan terlarang, ini jelas perlu ditekankan karena memiliki dampak negatif yang akan ditimbulkan bagi peserta didik yang mengalami hal tersebut (baik korban maupun pelaku).…”
Section: Hasil Dan Pembahasanunclassified
“…Misi yang keempat adalah meningkatkan keterampilan belajar efektif, ini berkaitan dengan bimbingan belajar. Menurut Santi et al (2017) Berdasarkan hasil wawancara bahwa terkadang ada peserta didik yang datang bukan berdasarkan pada kebutuhan yang telah di asesmen, maka setidaknya guru BK perlu memiliki berbagai kompetensi konselor sehingga hal tersebut bisa ditangani dengan baik. Selain itu, aspek kebutuhan lain yang tidak kalah penting adalah bagaimana mendukung program pemerintah melalui Kurikulum Merdeka dengan mencegah terjadinya 3 dosa besar Pendidikan seperti bullying, kekerasan seksual, dan intolerasi, ditambah dengan pencegahan terhadap obat-obatan terlarang, ini jelas perlu ditekankan karena memiliki dampak negatif yang akan ditimbulkan bagi peserta didik yang mengalami hal tersebut (baik korban maupun pelaku).…”
Section: Hasil Dan Pembahasanunclassified
“…Particularly, it is more problematic in the assembled parts such as B pillar in automobiles. Factors such as punch radius, lubricant, punch speed, crushing force, dwell time, grain size, thickness are effective on springback [18][19][20][21][22]. Various strain rates are used for forming sheet metal.…”
Section: Tensile Testmentioning
confidence: 99%
“…In another study, it is shown that the increase of the punch speed at three different high-strength steel almost does not affect the springback in the bending process using the V-die [18]. Kiswanto et al [19] performed a springback study on different parameters in the V bending die. They showed that with the increase of the punch speed, the amount of springback decreased.…”
Section: Tensile Testmentioning
confidence: 99%
“…Micro sheet metal forming is one of the most popular fields to be observed since it has been widely applied in producing micro-parts. Micro-bending is one of the basic forming processes that produce a micro-component with 3D contours, such as contacts/switches for micro-electrics , mechanical sensors, and housing for optical devices (Kiswanto et al, 2017). In sheet metal manufacturing technology, bending is defined as a straining process of flat strip material around a linear axis (Qin, 2010).…”
Section: Introductionmentioning
confidence: 99%